1998
DOI: 10.1016/s0378-1097(98)00043-3
|View full text |Cite
|
Sign up to set email alerts
|

Histidine utilisation operon (hut) is upregulated at low temperature in the antarctic psychrotrophic bacterium Pseudomonas syringae

Abstract: The antarctic psychrotrophic bacterium Pseudomonas syringae was mutagenised using a transposon Tn5-OT182 which facilitates identification of promoter fusions expressing the reporter gene (lacZ) for L-galactosidase. Most mutants expressed Lgalactosidase both at optimal growth temperature (20^22³C) and at low temperature (4³C). But a small percentage of the mutants (V5%) were unique in that they expressed L-galactosidase activity predominantly at low temperature. One such mutant was found to have an insertion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In addition, low temperature results in elevated expression of the ␣-glucan branching enzyme GlgB (YE4013) that, together with the ␣-amylase GlgX and GlgC, regulates the glycogen metabolism (56). Interestingly, the degradative hut operon, as well as an ␣-amylase, have been shown to be upregulated at low temperature in several antarctic psychrotrophic bacteria (23,36). A role of the Y. enterocolitica alkaline serine protease, a hot spot of mini-Tn5 luxCDABE insertions and a member of the extracellular subtilisin family (67), has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low temperature results in elevated expression of the ␣-glucan branching enzyme GlgB (YE4013) that, together with the ␣-amylase GlgX and GlgC, regulates the glycogen metabolism (56). Interestingly, the degradative hut operon, as well as an ␣-amylase, have been shown to be upregulated at low temperature in several antarctic psychrotrophic bacteria (23,36). A role of the Y. enterocolitica alkaline serine protease, a hot spot of mini-Tn5 luxCDABE insertions and a member of the extracellular subtilisin family (67), has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…About 5% of the genes expressed at 20°C by an Antarctic psychrotrophic Pseudomonas syringae strain are expressed at significantly higher levels at 4°C (68). The histidase and urocanase genes are among them, with urocanase activity being 14-fold higher in cells grown at 4°C than at 20°C, in marked contrast to the result seen with a mesophilic pseudomonad, where a lower temperature resulted in lower urocanase activity (68).…”
Section: Pseudomonadsmentioning
confidence: 93%
“…About 5% of the genes expressed at 20°C by an Antarctic psychrotrophic Pseudomonas syringae strain are expressed at significantly higher levels at 4°C (68). The histidase and urocanase genes are among them, with urocanase activity being 14-fold higher in cells grown at 4°C than at 20°C, in marked contrast to the result seen with a mesophilic pseudomonad, where a lower temperature resulted in lower urocanase activity (68). The mechanism responsible for this increased activity at low temperatures is unknown, but it operates at the transcriptional level and may reflect a cold-active promoter upstream from the normal promoter that operates at both temperatures (64).…”
Section: Pseudomonadsmentioning
confidence: 99%
“…Neither is any information available for the in vivo recognition of promoter sequences by RNA polymerase from the cold-adapted P. syringae. Therefore, we initially attempted to identify the genes from the Antarctic P. syringae that are upregulated at low temperature, with the help of Tn5-mediated random genomic fusions of a promoter-less reporter gene, lacZ (23). One of the fusions that produced at least 10-to 14-fold more ␤-galactosidase at a low temperature (4°C) was identified by cloning and sequencing of ca.…”
mentioning
confidence: 99%
“…450 bp of DNA sequence proximal to the Tn5 insertion site. The fusion was in the hutU gene, which encodes an enzyme, urocanase, of the histidine utilization pathway of bacteria (13,23). A direct assay of urocanase activity from the P. syringae and a few more Antarctic Pseudomonas species and comparison of it with that of the mesophilic Pseudomonas putida suggested that the hutU gene is upregulated in the psychrotrophs but not in the mesophile.…”
mentioning
confidence: 99%